2009
DOI: 10.1128/jcm.01313-08
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Comparison of PE and PPE Genes in the Mycobacterium avium Complex

Abstract: The Mycobacterium avium complex (MAC) comprises genomically similar but phenotypically divergent bacteria that inhabit diverse environments and that cause disease in different hosts. In this study, a wholegenome approach was used to examine the polymorphic PE (Pro-Glu) and PPE (Pro-Pro-Glu) gene families, implicated in immunostimulation and virulence. The four major groups of MAC organisms were examined, including the newly sequenced type strains of M. intracellulare and M. avium subsp. avium, plus M. avium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 58 publications
2
39
0
2
Order By: Relevance
“…The lack of extra clusters would indicate that apart from the specific SNPs, the target sequence is conserved. Regarding the three MAC reference strains tested, the preliminary results obtained with HRM analysis were in agreement with former in silico comparison of the MAP1506 sequences in M. avium subspecies avium and M. avium subspecies hominissuis (12). Accordingly, HRM analysis distinguished only M. avium subspecies paratuberculosis types II and III from a cluster containing the MAC strains and M. avium subspecies paratuberculosis type I isolates (see Fig.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The lack of extra clusters would indicate that apart from the specific SNPs, the target sequence is conserved. Regarding the three MAC reference strains tested, the preliminary results obtained with HRM analysis were in agreement with former in silico comparison of the MAP1506 sequences in M. avium subspecies avium and M. avium subspecies hominissuis (12). Accordingly, HRM analysis distinguished only M. avium subspecies paratuberculosis types II and III from a cluster containing the MAC strains and M. avium subspecies paratuberculosis type I isolates (see Fig.…”
supporting
confidence: 72%
“…One of the members of this family, MACPPE23 (MAP1506) contains M. avium subspecies paratuberculosis type-specific SNPs in its sequence (12). Previously, these SNPs were used as a target to type M. avium subspecies paratuberculosis isolates by DGGE (10).…”
mentioning
confidence: 99%
“…PE/PPE genes are less abundant in MAP than other mycobacterial species but are thought to influence antigenic diversity, virulence, host adaptation and growth in macrophages (Mackenzie et al, 2009). Zhu et al (2008) reported significant up-regulation of MAP PE4 (MAP1507) and PE (MAP1003c) genes post infection into bovine monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…T he members of Mycobacterium spp., comprising the Mycobacterium avium complex (MAC) consist a very interesting group in terms of ecology, differing in virulence and ecology and are the most frequently isolated nontuberculous mycobacteria (Mackenzie et al, 2009). The MAC comprises slow-growing mycobacteria that are ubiquitous in the environment (soil and water) and have a wide source range, causing disease in various mammals and birds (Mackenzie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The MAC comprises slow-growing mycobacteria that are ubiquitous in the environment (soil and water) and have a wide source range, causing disease in various mammals and birds (Mackenzie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%